European and Greek legislation on preschool children's protection from the use of unsafe toys - Katsikonouri, Effrosyni; Riga, Vassiliki (Preschool and Primary Education, 2014)
The present study attempts to examine the impact of laws and legislation on the safe construction of toys and their use by young children. The research hypothesis was that the European Union (EU) and its Member States, particularly Greece, implement administrative measures and penalties for the withdrawal of unsafe toys and inform consumers. Content analysis of European and Greek legislation, notifications and penalties imposed on offenders was used to test the hypothesis and the research objectives. The results showed an excessive number of violations of toy safety standards notified to Member States of the EU through the RAPEX system. Greece, despite delayed harmonisation with EU directives and poor information provided to consumers (parents, teachers, children's caregivers, toy librarians), has taken measures to restrict or prevent the distribution of faulty products.